Efficacy and safety of massage for postoperative stress in colorectal cancer patients: a randomized, controlled, three-arm trial - Werthmann, Paul G.; Cysarz, Dirk; Jungbluth, Melanie; Lederer, Ann-Kathrin; Nenova, Gergana; Huber, Roman; van Dijk, Monique; Kienle, Gunver S. (Frontiers in Oncology, 2025)
PurposeThe purpose of this study was to investigate the effect of rhythmic embrocation (RE), a massage technique, on postoperative stress levels (measured by heart rate variability) in colorectal cancer surgery patients compared to empathic conversation.MethodsThe study included 68 patients who were randomized into three groups: one received RE from professionals, another from students, and the third received empathic conversations. Stress was quantified using heart rate variability before and after the interventions.ResultsThe standard deviation of the heartbeat intervals (SDNN) increased more in the professional RE group 9.12 ms (IQR 3.59-12.3 ms) than in the other groups: student RE group 5.68 ms (-0.66-7.5 ms), empathic conversation group 6.64 ms (-1.49-7.38 ms); hence stress decreased more in the professional RE group, although not statistically significant (p= 0.21). Other factors like sleep quality, nausea, pain, and mood did not differ significantly between the groups. No complications were associated with the interventions.ConclusionRE was safe and a statistically significant superiority of RE on postoperative stress compared to empathic conversations could not be found. Due to high inter- and intraindividual variability a clear pattern of response of the secondary outcomes to RE in comparison to empathic conversations could not be found. The study was limited by a small sample size, high patient variability, effective co-interventions for sleep, pain and nausea, and by an imbalance between groups. The study indicates that future research on RE should focus on a more narrowly defined patient population, increase the sample size, and select comparison groups that are clearly distinct from each other as well as a clinical context with fewer confounding factors. Furthermore, the patient’s preferences and previous experiences with massage therapy should be considered.Clinical trial registrationGerman Clinical Trials Register (www.drks.de), identifier DRKS00023407.